Bioactive and ACE binding properties of three synthetic peptides assessed by various spectroscopy techniques. Issue 12 (December 2016) - Tanzadehpanah, Hamid; Asoodeh, Ahmad; Mahaki, Hanieh; Mostajabodave, Zeinab; Chamani, Jamshidkhan; Mojallal-Tabatabaei, Zahra; Emtenani, Shirin; Emtenani, Shamsi; Moradi, Mohammad-Reza
Graphical abstract: Highlights: Antioxidant, cytotoxicity, ACE inhibitory/interactions of 3 peptides were studied. P2 peptide showed high efficiency in inhibition of ACE (IC50  = 97 μg/mL). Fuorescence spectroscopy showed that P2 had more affinity to ACE than P1 and P3. Peptides demonstrated no hemolytic activity and cytotoxicity against PBMC. Abstract: Peptides play an important role in metabolic regulation. In this study, one primary peptide derived from ostrich egg white protein hydrolysate and its truncated fragment and analogue were chemically synthesized. Peptide sequences were as follows: LTEQESGVPVMK (1317.54 Da, P1) with truncated fragment TEQESGVPVM (1076.187 Da, P2), and analogue TEQESGVH VM (1116.22 Da, P3). The antioxidant, angiotensin-converting enzyme (ACE) inhibitory, hemolytic activities and cytotoxicity of these peptides were investigated in vitro. The results showed that P3 has a potent antioxidant activity. The analogue peptide (P2) showed high efficiency for the inhibition of ACE (73% with IC50  = 97 μg/mL). Fluorescence spectroscopic study of the interaction between the peptide and ACE showed that P2 had more affinity to ACE than P1 and P3. The results of circular dichroism (CD) showed that the significant conformation changes of ACE were related to P2 (unordered coil from 7.94 to 21.24%). Moreover, the synthetic peptides showed virtually no hemolytic activity and cytotoxicity against human peripheral blood mononuclear cells (PBMCs). Our results suggested that truncate and a proline-to-histidine substitution in the sequence could be useful to increase the efficiency of bioactive peptide.